Impact of the COVID-19 Pandemic on Airport And Airline Digital Transformation - Anna SZYMCZAK (Communications of International Proceedings, 2021)
In 2020 airlines slashed their IT investment plans to mitigate the revenue drop caused by the COVID-19 pandemic. The ACI and SITA survey results show that airports spent on IT solutions - 5.46% of revenues in 2020, which was about USD 3.5 billion (EUR 3 billion). The main emphasis was on the program to increase the efficiency of airport operations and ensuring the availability of safer and automated processes. In the last year, airlines have doubled implementations and plan to double investment on self-boarding using biometric & ID documentation. In response to the pandemic, most airlines will invest more in in-house virtual and remote IT services. The paper attempts to obtain a formal description of the digital transformation taking place in civil aviation with an indication of specific concepts - Airport 1.0 to Airport 4.0. The article was based on reports and research conducted both before and during the COVID-19 pandemic.
Keywords: Digital Transformation; Aviation; Airports; Airlines